Poder y violencia en las comunidades indígenas brasileñas - Wenczenovicz, Thaís Janaina (2017)
The purpose of this study is understand the violence against indigenous peoples in contemporary Brazil, it is necessary from a systemic and long-term analysis, considering their interrelationship with power. Power used in the process of occupation and settlement, in the disputes over land, or in the process of settlement, acculturation and assimilation. For this analysis it is necessary to understand the violence from the Colonialidade of power, with the independence of the colonies of the Iberian Empires, the colonial power remained.